Seeds of latent hope: the figurative entwinement of children, adolescents, and plants in Maja Lunde’s "The Dream of a Tree" - Guanio-Uluru, Lykke (Ecozon@: European Journal of Literature, Culture and Environment, 2023)
Drawing on theorizations and previous studies of climate fiction, perspectives from critical plant studies, and discussions on the mythical and symbolic role of trees and seeds, this study traces figurative relationships between plants and the child- and adolescent characters in Maja Lunde’s latest climate fiction, "The Dream of a Tree" ("Drømmen om et tre", 2022). The novel is the last volume in Lunde’s “climate quartet”, where she, for the first time in her series, employs a young adult protagonist. The plot revolves around a group of children, stranded on the archipelago of Svalbard that hosts the global seed vault. The study aims to show how the child and adolescent characters in Lunde’s climate fiction are embedded in figurative patterns associating them with growth and hope in ways that serve to move Lunde’s climate quartet from a dystopian towards a more utopian resolution. Recurriendo a teorizaciones y estudios previos sobre ficción climática, a perspectivas de estudios críticos de las plantas, y a debates sobre el papel mítico y simbólico de los árboles y las semillas, este estudio traza las relaciones figurativas entre plantas y los personajes infantiles y adolescentes en la ficción climática más reciente de Maja Lunde, "The Dream of a Tree" ("Drømmen om et tre", 2022). La novela es el último volumen del “cuarteto climático” de Lunde, en la que, por primera vez, la autora utiliza un protagonista adolescente. El argumento gira en torno a un grupo de niños varados en el archipiélago de Svalbard que acoge el banco mundial de semillas. Este estudio pretende mostrar cómo los personajes infantiles y adolescentes en la ficción climática de Lunde están incrustados en patrones figurativos que los asocian con crecimiento y esperanza de formas que sirven para trasladar el cuarteto climático de Lunde de una resolución distópica a una más utópica.